Kinematic durability of chain trans fer with the tooth chain andthe evolvment asterisk - O.I. Ostapenko; A.A. Voina; R.L. Lichman (Advanced Engineering Research, 2009)
In the article the application of tooth chains, their structure and deterioration is described, the maximum permissible increase in a step of a chain on gearing with evolvment asterisk is found. The dependence of tooth chain deterioration graph for rectilinear and evolvment chain-wheel profile is constructed